관계 욕구 척도의 개발 및 타당화 - 강수현(Soo-Hyun Kang); 김정호(Jung-Ho Kim); 김미리혜(Mirihae Kim) (Seuteureseu yeon-gu (Online), 2019)
본 연구의 목적은 관계욕구가 접근-회피 개념으로 나누어지고 서로 독립적이라는 선행연구에 근거하여 한국형 관계욕구 척도를 개발하고 타당화하는 것을 목적으로 하였다. 일련의 과정을 통해 예비 문항들을 표집 후 문항 분석하여 탐색적 요인 분석을 통해 접근-회피 개념이 독립된 개념임을 확인하였다. 그 결과 접근-관계 욕구는 ‘친밀 관계 경향성’의 1요인 모형으로 6문항, 회피-관계 욕구는‘타인의 평가에 대한 민감성’과 ‘부정적 평가에 대한 민감성’,‘타인의식’의 3요인 모형으로 11문항인 총 17문항의 관계 욕구척도를 개발하였다. 본 연구 결과를 통해 한국형 관계욕구 척도가 신뢰롭고 타당한 척도임을 확인할 수 있었으며, 끝으로 본 연구의 의의와 제한점 및 추후 연구에 대한 제언이 논의되었다. Background: The purpose of this study was to develop and validate the relational need scale. Based on previous studies, we presumed that relational need is comprised of the two independent concepts of approch and avoidance. Methods: The preliminary items were selected through a series of processes and they were analyzed in terms of item content, response distribution and correlations with other measures. Exploratory factor analysis confirmed that approach and avoidance concepts were independent from each other. Results: As a result, the relational need scale was developed, consisting of 6 approach-type items for the relational need subscale and 11 items for the avoidance-type subscale. The two subscales are each subsumed by a one-factor model and a three-factor model, respectively. Specifically, the approach-type subscale has subfactors of 'Intimate relationship tendency', whereas the avoidance-type subscale has the subfactors of 'sensitivity to others evaluations,' 'sensitive to negative evaluations,' and 'awareness for others'. Conclusions: The internal consistency, test-retest reliability, and criterion-related validity of the scales were found to be adequate. This study revealed that the Korean version of relational need scale is reliable and valid. Finally, implications and limitations of this study and suggestions for future studies are discussed. KCI Citation Count: 1